Analisis Yuridis Terhadap Permohonan Perwalian Anak Yang Tidak Dapat Diterima Oleh Pengadilan Negeri Yang Menimbulkan Kerugian Bagi Anak - Daim, Nuryanto A.; Abadi, Suwarno (Universitas Wijaya Putra, 2023)
A child who is not under the authority of his parents who apparently does not have a guardian, either one person, then in this case the judge can appoint through a court order, namely a guardian at the request of certain parties who have an interest. The exception is when the parents who live the longest include in their will (testament) to appoint or appoint a guardian for their child, then it is called a trusteeship according to a will. Trusteeship is an institution that replaces parental authority over children who have not reached a certain age (age) or are not yet married. The aim of the study was to analyze the basis for the judge's considerations in deciding the civil case Number 134/Pdt.P/2020/PN Prp which stated that it could not accept the application submitted by the applicant, which caused harm to the child. By using normative juridical methods and statutory approaches, concepts and case study approaches, the results of the research found that the basis for the judge's considerations in deciding civil cases Number 134/Pdt.P/2020/PN.Prp stated that they could not accept a request that filed by the applicant, what caused harm to the child was the consideration that during the trial the Petitioner never submitted evidence explaining HS 's heirs, then knowing the fact that there was another person who had arranged for HS 's inheritance certificate, giving rise to suspicion that someone else had become heirs of HS and there is no evidence stating that HS 's heirs other than EV are not willing to become the guardians of EV , so it is not yet possible to determine whether the Petitioner has the legal right to apply for guardianship of EV , therefore the Petitioner's petition cannot be accepted.